2013
DOI: 10.1371/journal.pone.0053576
|View full text |Cite
|
Sign up to set email alerts
|

ES Micro-Environment Enhances Stemness and Inhibits Apoptosis in Human Limbal Stem Cells via the Maintenance of Telomerase Activity

Abstract: Our previous work had found that telomerase rejuvenated in the cytoplasm of corneal epithelial cells cultured in embryonic stem cell-conditioned medium, the functional properties of stem-like corneal epithelial cells can be enhanced by co-culturing with embryonic stem cells (ESCs) via activation of the integrinβ1-FAK-PI3K/Akt signaling pathway. The goal of this study was to explore the potential molecular mechanisms of the ES micro-environment that enhance the stem cell-like phenotype and inhibit apoptosis in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 46 publications
2
17
0
Order By: Relevance
“…We have considered two aspects in our studies: (1) cellular microenvironment: embryonic stem cell microenvironment culture systems can make the differentiated corneal epithelial cells, conjunctiva epithelial cells [15] and even human corneal endothelial cells [17] obtain a strong proliferation ability and can be passaged long-term with de-differentiation cell marker expression, normal cell morphology and karyotype, but no tumorigenicity. Our preliminary findings showed that the ES microenvironment may inhibit the apoptosis of the cells by activating telomerase via integrin the b1-FAK-PI3K/Akt, telomerase-p21-mitochondrial axis and FAK/Wnt signaling pathway [18,144] ; and (2) stromal microenvironment: the APCS limbal produced by lipase (not existing protease digestion) [25,30] can retain the normal extracellular matrix, collagen lamellar micro ultrastructure. It can repair and maintain the stemness and proliferation ability of the limbal stem cells after it is transplanted to the limbal stem cell deficiency rabbit model.…”
Section: Progress In the Research Of Stem Cell Therapy For Corneal DImentioning
confidence: 90%
“…We have considered two aspects in our studies: (1) cellular microenvironment: embryonic stem cell microenvironment culture systems can make the differentiated corneal epithelial cells, conjunctiva epithelial cells [15] and even human corneal endothelial cells [17] obtain a strong proliferation ability and can be passaged long-term with de-differentiation cell marker expression, normal cell morphology and karyotype, but no tumorigenicity. Our preliminary findings showed that the ES microenvironment may inhibit the apoptosis of the cells by activating telomerase via integrin the b1-FAK-PI3K/Akt, telomerase-p21-mitochondrial axis and FAK/Wnt signaling pathway [18,144] ; and (2) stromal microenvironment: the APCS limbal produced by lipase (not existing protease digestion) [25,30] can retain the normal extracellular matrix, collagen lamellar micro ultrastructure. It can repair and maintain the stemness and proliferation ability of the limbal stem cells after it is transplanted to the limbal stem cell deficiency rabbit model.…”
Section: Progress In the Research Of Stem Cell Therapy For Corneal DImentioning
confidence: 90%
“…In recent years, the discovery of telomere-independent effects of TERT on proliferation [87][88][89][90][91][92][93][94][95] and perturbations of resistance to reactive oxygen species damage [96][97][98][99][100] have led to a burgeoning body of evidence that indicates that TERT has many functions outside it's canonical role in telomere length maintenance. 101 Some of these extra-telomeric effects include acting as an RNAdependent RNA polymerase, 102 a mitochondrial reverse transcriptase, 103 interacting with nucleostemin (GNL3), 104 WNT, BRG1, b-catenin, 87,105 NF-kB, 106 and modulating endogenous siRNA 102,107 and miRNA profiles.…”
Section: Non-canonical Functions Of Telomerase and Pluripotencymentioning
confidence: 99%
“…TERT is capable of aiding the maintenance of self-renewal in human limbal and mesenchymal stem cells, increasing the efficiency of directed differentiation, 48,99 enhancing iPSC reprogramming efficiency 40 and activating resting hair follicle stem cells. 90 Several recent reports have shown that TERT is able to interact with BRG1 in a WNT/b-catenin dependent manner.…”
Section: Tert Brg1 and Wntmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have shown that LSCs undergo more frequent cell divisions than terminally differentiated corneal epithelial cells (TDCs) and could be cultured ex vivo from limbal tissues (Liu et al. ), which could represent a source of cells for transplantation in the treatment of LSCs deficiency (LSCD) (Rama et al. ; Chae et al.…”
Section: Introductionmentioning
confidence: 99%